2009
DOI: 10.1016/j.otohns.2008.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Otitis media with effusion: A possible role for Helicobacter pylori?

Abstract: The current study confirms the presence of Helicobacter pylori in the nasopharynx and middle ear space, but our results do not support a role for this bacterium in the pathogenesis of otitis media with effusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 4 publications
0
15
0
1
Order By: Relevance
“…8,9 Similar to our study Fancy et al confirmed the presence of H. pylori in the nasopharynx and middle ear space, but Ozcan et al was unable to detect the presence of H. pylori in the middle ear effusions and adenoid specimens of children with 'chronic otitis media with effusion'. 10,11 There were relatively important findings by Iriz et al found presence of H. pylori tested in all tympanosclerosis biopsies, and by Yazdi et al that auditory recovery in GERD positive patients was significantly lower, even six months after surgery and thus suggesting evaluation for GERD an important procedure before tympanoplasty. 12,13 Regurgitation and heartburn have been reported to be other common features of GERD along with pathologic acid flux.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Similar to our study Fancy et al confirmed the presence of H. pylori in the nasopharynx and middle ear space, but Ozcan et al was unable to detect the presence of H. pylori in the middle ear effusions and adenoid specimens of children with 'chronic otitis media with effusion'. 10,11 There were relatively important findings by Iriz et al found presence of H. pylori tested in all tympanosclerosis biopsies, and by Yazdi et al that auditory recovery in GERD positive patients was significantly lower, even six months after surgery and thus suggesting evaluation for GERD an important procedure before tympanoplasty. 12,13 Regurgitation and heartburn have been reported to be other common features of GERD along with pathologic acid flux.…”
Section: Discussionmentioning
confidence: 99%
“…Iriz et al ( 26 ) showed that there are similar risk factors, such as increased homocysteine levels, between coronary artery atherosclerosis and tympanosclerosis. Although tympanosclerosis and atherosclerosis are two separate pathologies, they have similar histological and pathophysiologic elements and the same genetic reason has been proposed for both ( 2 ). Ameriso et al ( 30 ) studied evidence concerning the development of inflammation caused by H. Pylori in 38 patients with atherosclerotic plaques who had undergone endarterectomy and found that in most of these patients H. Pylori was correlated to the inflammation, which indicated the correlation between H. Pylori and atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Helicobacter pylori is a Gram-negative, spiral and microaerophilic microorganism that was first isolated from the stomach of patients afflicted with peptic ulcer ( 1 , 2 ). This bacterium can cause gastritis and peptic ulcer in the short-term and carcinoma of the stomach in the long-term ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Then 20 studies were further excluded by the inclusion criteria, including 10 case series studies, 6 animal experiment studies, 3 studies that lacked original data, and 1 duplicate study. Ultimately, a total of 11 case-control studies in 9 different articles [11][12][13][14][15][16][17][18][19] were included in our current meta-analysis. The progress of the literature search is shown in Figure 1.…”
Section: Literature Searchmentioning
confidence: 99%